Análise de viabilidade técnica da conservação de água no cilo produtivo de indústria de refrigerante - CUNHA, Bruno José Costa da (Universidade Federal do Pará, 2019)
This work aims to formalize an engineering protocol containing technical procedures necessary to optimize the consumption of water in the beverage industry, through the evaluation of the potential of water conservation, determination of environmental and economic performance indicators, as well as the proposition of scenarios of water use. In order to explore the opportunities for water conservation, a water balance was carried out with the help of flow measurement methods. Water use analyzes were performed to determine areas and processes where there is significant potential for water savings. Based on the evaluations, investigations, recycling and reuse practices it was observed that the productive sector of the soft drink factory, especially the packaging stage, has the potential to reduce water consumption. The proposed scenarios can provide the company with a reduction in specific water demand from 2.53 to 1.92m³/m³refrigerants, reducing the company's groundwater abstraction by 24.1%. Thus, considering the average production of refrigerants, the daily water savings can be up to 81.4m³, while the company's specific effluent generation can be reduced by 36.7 m³ / d, equivalent to 24, 1% reduction. In addition, the operating costs of the ETE and ETA can be reduced by R$ 39,272.83 per year, representing a savings of 24.5%. Thus, this study proved that water reuse can be successfully implemented in the soft drink industry as a sustainable approach to industrial water management, since the engineering protocol established in this work proved adequate for the collection of information necessary for the control and optimization of water use.